Effects of microplastics pollution in sediments on physicochemical properties and microbial community distribution in coastal Spartina alterniflora-invaded wetlands - Guo Li; Jiao Ran; Jing Dong; Kai Yang; Jingru Hu; Jing Shi; Yumiao Zhang; Jiabin Chen; Yu Zhao; Ensheng Zhu; Suzhen Huang; Zheng Zheng (Frontiers in Marine Science)
IntroductionCoastal wetlands play an important role in the global ecosystem, yet they are increasingly facing ecological degradation due to pollution and the spread of invasive Spartina alterniflora (S. alterniflora). Among the environmental challenges, microplastics (MPs) contamination in S. alterniflora-invaded coastal wetlands is of growing concern. However, the effects of MPs pollution in S. alterniflora-invaded coastal wetlands are not clear.MethodsThis study investigated the effects of S. altemiflora invasion on the distribution of MPs and the effects of MPs pollution on the physicochemical properties of sediments and the structure of microbial communities in the Tiaozini wetland of Jiangsu Province, China.Results and discussionThe total MPs abundance of the S. altemiflora single-plant area was the highest (16.338 x103 items/kg d.w.). Polyurethane and Chlorinated polyisoprene are typical MPs types in the study area. Polyurethane exhibits high abundance at all sampling sites, while Chlorinated polyisoprene is one of the dominant MPs types in the single-plant and sub-mature area of S. alterniflora. The results showed that the invasion of S. alterniflora promoted the accumulation of MPs in the sediments of the coastal wetland. This accumulation increased the total organic carbon (TOC), available phosphorus (AP) and total nitrogen (TN) contents. Moreover, MPs pollution increased the ALP and SUC enzyme activities of sediment. In addition, MPs contamination increased the abundance of Proteobacteria and Bacteroidota in the sediments. This study highlights the complex interactions between MPs pollution and S. alterniflora invasion, providing the foundation for understanding the synergistic impacts of these stressors on coastal wetland ecosystems.